QUALITY OF MEMBERS OF THE INDONESIAN POSITIVE WOMEN'S ASSOCIATION (IPPI) WHO LIVE WITH HIV/AIDS IN BANDUNG INDONESIA - Titik Dewi Astuti; Admiral Nelson Aritonang (Politeknik Kesejahteraan Sosial Bandung, 2022)
Quality of life is an individual’s perception of his life in society in the context and existing value systems related to goals, expectations, standards and also defenses against life. Quality of life refers to aspects of physical health, psychological conditions, social relations and the informant’s expectations of current life. The research method used is the descriptive qualitative research method. The technique used is by conducting in-depth interviews and documentation studies. Determination of informants using purposive sampling totaling 7 informants. Testing the validity of the data using angulated sources and thecniques, referential adequacy, and persistence of observations. Data analysis techniques by doing data reduction, data display, and also make conclusions. The result showed that women with HIV/AIDS in Ikatan Perempuan Positif Indoensia (IPPI) had a fairly good quality of life . Physical health, psychological aspects and social relations show good results. Environmental aspects of the informants were unable to fulfill their needs due to lack of access to work and lack of skills.